39‐1: Invited Paper: Thick‐Shelled Quantum Dots for Display Applications. Issue 1 (2nd June 2017) - Chen, Chih-Jung; Lien, Jiun-Yi; Wang, Sue-Lein; Chiang, Ray-Kuang
Abstract : Quantum dots (QDs) with highly pure emission color are superior to other fluorescent materials used in wide‐color‐gamut displays. To further improve the efficiency of these systems, in which QDs are pumped by the LED chips, QDs with properties such as high quantum yield, high activation‐light absorption, low self‐quenching, high photostability, and high thermal stability are desired. II‐VI QDs with thick shells (> 10 monolayers), which simultaneously reach small lattice strains and low band gap offset, endorse QDs to work in a thin and densely packed film at caustic operating conditions due to their low internal defects, large size, and "soft" or "smooth" potential well of confinement. Thick‐shelled QDs for both photoluminescent and electroluminescent applications can be prepared by multiple interfusions of different shell materials to ensure their performance.